Advancing Nanoscale Copper Deposition Through Ultrafast-Laser-Activated Surface Chemistry - Modestas Sadauskas; Romualdas Trusovas; Evaldas Kvietkauskas; Viktorija Vrubliauskaitė; Ina Stankevičienė; Aldona Jagminienė; Tomas Murauskas; Dainius Balkauskas; Alexandr Belosludtsev; Karolis Ratautas (Nanomaterials)
Direct-writing submicron copper circuits on glass with laser precision—without lithography, vacuum deposition, or etching—represents a transformative step in next-generation microfabrication. We present a high-resolution, maskless method for metallizing glass using ultrashort pulse Bessel beam laser processing, followed by silver ion activation and electroless copper plating. The laser-modified glass surface hosts nanoscale chemical defects that promote the in situ reduction of Ag+ to metallic Ag0 upon exposure to AgNO3 solution. These silver seeds act as robust catalytic and adhesion sites for subsequent copper growth. Using this approach, we demonstrate circuit traces as narrow as 0.7 µm, featuring excellent uniformity and adhesion. Compared to conventional redistribution-layer (RDL) and under-bump-metallization (UBM) techniques, this process eliminates multiple lithographic and vacuum-based steps, significantly reducing process complexity and production time. The method is scalable and adaptable for applications in transparent electronics, fan-out packaging, and high-density interconnects.